(untitled) (Research, Society and Development, 2021)
Objectives: To analyze the contributions of realistic simulation as opposed to traditional nursing undergraduate education. Specific objectives: aim to describe the advantages of realistic simulation as a teaching strategy for nursing education; identify the realistic simulation techniques used as a teaching strategy for the nursing course and identify the effectiveness of using realistic simulation in the teaching-learning process. Method: This is a descriptive study of the systematic literature review type. A final sample of 17 studies published in the last five years in the following databases MEDLINE, LILACS and BDENF was analyzed. With the population of undergraduate nursing students. Results: Realistic simulation, unlike traditional teaching, allows for an approximation between reality and theory, helping to build skills, knowledge and reducing risks. It helps the apprentice to develop autonomy, confidence and critical thinking in their clinical practices. It is a better learning strategy, as it adds several benefits to the student through the application of the active methodology.